Keputusan pembelian konsumen: Dampak harga, lokasi, kualitas produk, dan citra merek - Rahmah, Nailatur; Subqi, Tajus (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2024)
The culinary industry is constantly evolving with numerous opportunities. A prime example is the Tok Patok Ganding restaurant, located strategically in high-traffic areas and offers high-quality products at affordable prices. This study explores the factors influencing consumer buying decisions, focusing on price, location, product quality, and brand image. The research was conducted at the Tok Patok Ganding branch using a quantitative approach. The sample included 96 customers selected using the Lemeshow formula and the Accidental Sampling method. The research participants were customers of the Tok Patok Ganding branch. Data was gathered through surveys and observational tools. The data was analyzed using SPSS 21 software through multiple linear regression analysis. The results indicate that price, location, product quality, and brand image positively impact purchasing decisions, individually and collectively. This forms the main conclusion of the study.